Empirical modelling of variable capacity air-to-air heat pumps in trnsys. Issue 5 (3rd September 2022) - Strugala, Gregor; Kummert, Michaël; Kegel, Martin
Abstract : Variable capacity heat pumps improve seasonal performance and operate at lower temperatures by varying their compressor speed to match their capacity to a specific thermal load. They constitute a great asset in our struggle to lower energy consumption and carbon emissions, especially in cold climates. However, being a more recent and complex technology, they are not easily integrated in the design of building energy systems as adequate models are lacking. A trnsys model for variable capacity air-to-air heat pumps (vcaahp s) relying on performance maps and restricted to mini-split systems was therefore developed to streamline this design process and provide more accurate results. The model is presented first; it can reproduce most common heat pump behaviours – such as defrost and latent cooling. Then, a methodology relying on experimental data to supplement (often incomplete) manufacturer performance maps is provided. Finally, model usage is exemplified through a case study highlighting specific features and behaviours.